2017
DOI: 10.1186/s12863-017-0581-8
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of NETO2 gene in colorectal cancer

Abstract: BackgroundNeuropilin and tolloid-like 2 (NETO2) is a single-pass transmembrane protein that has been shown primarily implicated in neuron-specific processes. Upregulation of NETO2 gene was also detected in several cancer types. In colorectal cancer (CRC), it was associated with tumor progression, invasion, and metastasis, and seems to be involved in epithelial-mesenchymal transition (EMT). However, the mechanism of NETO2 action is still poorly understood.ResultsWe have revealed significant increase in the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 70 publications
2
11
0
Order By: Relevance
“…In our work, manipulation of NETO2 gene significantly changed not only the cell morphology but also the expression of mesenchymal and epithelial markers in GC cells, implying that induction of EMT was involved in NETO2-promoted invasion and metastasis of GC cells. However, Maria et al 34 reported that the elevated mRNA level of NETO2 in CRC was not directly correlated with expression of EMT-related genes. The reason for the discrepant results is not clear but may be may be attributed to the difference in tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…In our work, manipulation of NETO2 gene significantly changed not only the cell morphology but also the expression of mesenchymal and epithelial markers in GC cells, implying that induction of EMT was involved in NETO2-promoted invasion and metastasis of GC cells. However, Maria et al 34 reported that the elevated mRNA level of NETO2 in CRC was not directly correlated with expression of EMT-related genes. The reason for the discrepant results is not clear but may be may be attributed to the difference in tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that SMAD7 is present in common malignancies and acts as a tumor suppressor, including lung cancer, liver cancer, gastric cancer, bladder cancer, triple negative breast cancer, and osteosarcoma [11,[23][24][25][26][27][28]. In CRC, reduced level of SMAD7 is found to be involved in the process of cancer growth as well as the process of EMT and invasion [29]. Studies also show that SMAD7 gene polymorphisms are associated with CRC risk in patients with Lynch syndrome [30].…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies have mainly focused on its biological functions in neural-specific processes 7. However, subsequent reports have revealed that the expression of NETO2 is also found in several non-neural tissues, and recent studies have further indicated that NETO2 expression is associated with various cancers such as renal, lung, colon, cervical and colorectal cancer 8,9. In particular, a clinical study of the relationship between dysregulation of NETO2 expression and colorectal cancer progression has suggested that NETO2 upregulation is associated with poor prognosis and may function as a potential biomarker of advanced carcinoma progression 10.…”
Section: Introductionmentioning
confidence: 99%